THE EFFECT OF GENDER CHARACTERISTICS AND MATHEMATICS HABITS OF MIND ON STUDENTS' MATHEMATICS LEARNING OUTCOMES IN KENDARI - Halistin, Halistin; Patih, Tandri; Saputri, Rahma Okta; Cahyani, Evi Nur; Azia, Azia (IAIN Ambon, 2023)
This study aims to describe gender characteristics, describe Mathematics Habits of Mind, and determine the effect of gender characteristics and Mathematics Habits of Mind on mathematics learning outcomes. This study method uses a quantitative approach with the type of ex-post facto research. The gender characteristics questionnaire was adapted from the Bem Sex Role Inventory by Sandra L. Bem (1977), and the Mathematics Habits of Mind questionnaire was modified by Costa and Kallick (2008). While the results of learning mathematics are taken from the teacher's documentation of the results of students' daily tests. Based on the results of the research data analysis, it was found that 1) There were ten students with Feminine Gender, there were 34 students with Masculine Gender, there were 26 students with Androgyny Gender, and there 35 students with Undifferentiated Gender; 2) Mathematics Habits of Mind of students who are in the High category by 1.9% of students; 55.2% are in the Medium category, and 42.9% are in a Low category; 3) There is an effect of gender characteristics and Mathematics Habits of Mind on students' mathematics learning outcomes